Palaeo-Eskimo gathering site architecture: An example from Godthåb Fjord, Greenland - Appelt, Martin (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2003)
AbstractDuring the sixties, a number of large-scale archaeological surveys were conducted by the Danish National Museum in the Godthåb Fjord area on central west coast Greenland. The surveys led to extensive excavations including those of Saqqaq sites. However, descriptions of most of these sites have been preliminary published only, and the Palaeo-Eskimo settlement pattern of Godthåb Fjord has never been synthesized. The paper includes information on the Itinnera, Nuunnguaq and Tuapassuit sites, revealing both distinct intra-site similarities and variability. It is suggested that the Saqqaq site Tuapassuit is an aggregation camp, thus pushing evidence of this phenomenon several centuries further back in time than previously known.